Efeito anti-inflamatório do óleo fixo das sementes da Hancornia speciosa Gomes - Abreu, Fabíula Francisca de (2019)
Hancornia speciosa Gomes (mangabeira) is used in folk medicine to treat different diseases, including inflammatory conditions. Leaves and fruits have been extensively studied but there is no investigation on the biological effects of the fixed oil extracted from its seeds. The aim this study was evaluated the anti-inflammatory activity of the oil from “mangaba” seeds (OMS) in mice. Adult male Swiss mice (25-30 g) were used and the protocols were approved by the Ethics Committee for Animal Research (n°28/2018). Cytotoxicity was evaluated in fibroblasts of the L929 cell line through MTT assay. The topical anti-inflammatory activity was evaluated in the ear edema induced by 12-O-tetradecanoylphorbol-13-acetate (TPA). Treatment with OMS (0.3, 1.0 or 3.0 mg/ear) or dexamethasone (0.05 mg/ear, control) was concomitantly administrated with TPA (1 µg/ear) in the ipsilateral ear, topically. After 6 hours, edema, myeloperoxidase (MPO) activity, cytokine levels (TNF-α, IL-6 and IL-1β), histological alterations, vascular permeability and oxidative parameters were measured. The topical effect has also evaluated in the capsaicin-induced ear edema (0.2 mg/ear). In this model, animals were pre-treated with OMS (3 mg/ear) or ruthenium red (7.8 ng/ear, control) administrated in the ipsilateral ear 15 minutes before induction. After 30 minutes was measured ear edema. For evaluation of the systemic anti-inflammatory activity, mice were treated with vehicle (Tween 0.5% in saline, 10 mL/kg), OMS (100, 200 or 400 mg/kg, p.o. or i.p.) or dexamethasone (5 mg/kg, p.o. or s.c.) administered 1 hour or 30 min, respectively (for each route of administration), before intrapleural injection of carrageenan (1 mg/cavity). The fluid leakage from the pleural cavity was collected 4 h after induction for assessment of total leukocyte counts, MPO activity, protein extravasation and cytokine levels (TNFα, IL-6, IL-1β and IL-10). Results were expressed as mean ± S.E.M. and were evaluated by one-way ANOVA followed by Tukey's test, with p <0.05 considered as significant. Treatment with OSM did not alter the percentage of cells viability at any of the concentrations used compared to control. The topical administration of OMS reduced edema, IL-1β and protein extravasation, for 3 mg/ear, in ears inflamed by TPA. OMS also reduced MPO activity, levels of TNF-α and IL-6, for 1 and 3 mg/ear, in the same model. No differences were observed in oxidative parameters for the topical treatments of OMS. Pre-treatment by OMS at 3 mg/ear not reduced ear edema induced by capsaicin, suggesting that TRPV1 channels are not involved in anti-inflammatory activity of topical OMS. In the carrageenan-induced pleurisy, OMS (100 and 200 mg/kg, i.p.) reduced total leukocyte counts, myeloperoxidase activity, total protein concentration and TNF-α and IL-1β levels in pleural lavage. However, when administraded by v.o. did not prevent the rise of total leukocytes in the pleural cavity in the same model. Treatment with dexamethasone significantly reduced all parameters evaluated in both models. Therefore, this data show for the first time the pharmacological characterization of OMS and demonstrated that this possesses antiinflammatory activity, which highlights the potential of this preparation from H. speciosa.